Pembangunan Class Library untuk Domain Product Management di Aplikasi M-Commerce pada Android - Adam Mukharil Bachtiar; Arifin Bardansyah (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
Criteo reports that the use of M-Commerce in 2015 has increased about 15% - 26%, compared to 2014. In 2015, users access M-Commerce using mobile phone more often than other devices. Around 54% of those users use mobile app while 46% use mobile browser. In addition, there is an increase in conversion value of the number of users switching from mobile browser to mobile app by 120%. In all these activities, 286% of users focus on product viewing activities. This phenomenon requires software developers to develop M-Commerce in a short time. On the other hand, the developers need time to develop MCommerce. One of the time-consuming activities is the development of functions for product management. Based on the software development, there is one concept that can be used, which is class library. A class library is a collection of classes and methods that provide functionality as basis for building a system within a case domain. The first step in this research is to do domain analysis to acquire frozenspot, hotspot, and function mechanism that will be provided in class library. The result of the hotspot will be analyzed to obtain the nine basic functions in the domain of product catalog case in M-Commerce. These functions will be mapped into ten classes in a class library which will be tested using unit testing and integration testing that can be used by M-Commerce developers to accelerate the development of product management on M-Commerce.